Применение модифицированного способа лечения диабетической ретинопатии - Иванова, Н.В.; Ярошева, Н.А. (Таврический медико-биологический вестник, 2010)
Метою дослідження було підвищити ефективність лікування хворих з ДР на підставі застосування модифікованого способу лікування препаратом ліпофлавон за розробленою нами схемою. Обстежено 134 хворих (268 очей) з ДР, середній вік яких склав 39.7 ± 8.2 років. Установлено, застосування нового модифікованого способу лікування хворих у комплексі з ліпофлавоном дозволило знизити прозапальні цитокіни (IL-1 і TNF- ) на 17% і на 14,5% відповідно, підвищити функціональну активність зорового аналізатора (чутливість і лабільність) за показниками ПЕЧФ (поріг електричної чутливості за фосфеном) і КЧЗМФ (критична частота зникнення мерехтінь за фосфеном) (в 3 рази), і, як наслідок, покращенню зорових функцій в середньому на 0,2 од. (проти 0,1 при традиційній терапії), що свідчить про більшу ефективність нового модифікованого способу лікування хворих з ДР. Research objective was to increase efficacy of treatment of patients with diabetic retinopathy (DR) on the basis of application of the modified method of treatment by a preparation lipophlavon under the scheme developed by us. There were examined 134 patients (268 eyes) with DR whose middle age has made 39.7 ± 8.2 years. It is determined that application of the new modified method of treatment of patients in a complex with lipophlavon has allowed to decrease proinflammatory cytokines (IL-1 and TNF- ) on 17 % and on 14,5 % accordingly, to increase functional activity of the visual analyzer (sensitivity and lability) on indicators of threshold of electric sensitivity on phosphene and critical frequency of disappearance of flickerings on phosphene (in 3 times), and, as consequence, improvement of visual functions on the average on 0,2 units (against 0,1 at traditional therapy) that testifies about more efficacy of the new modified method of treatment of patients with DR.